Study the susceptibility of infection with Hepatitis type C for Covid – 19 patients in Baghdad District – Iraq - Hasanain Sahib Salih; Shatha M Ali Safar; Safa Tawfeeq Whaeeb (Zien Journals, 2023)
The corona virus as mentioned as SARS-Cov2 is a respiratory disease that causes a respiratory diseases and main responsible for the pandemic of corona in 2019 which started in Wuhan city- China and dispersed to the worldwide cases a million of infection among people in different countries, this study to showed the relationship between the patient infected previously with SARS-CoV2 and the possible infection to Hepatitis virus type C, the main causes of acute hepatitis. The patients tested from AL Yarmouk Hospital- Baghdad and ranged between 19-74 years old from both genders. The result showed no susceptible infection between the HCV disease and previous infection with corona disease.
Keywords: infection; HCV disease; Hepatitis; C